Pelatihan Penulisan Karya Ilmiah Siswa Kelas 12 SMA Islam Teratai Putih Global Bekasi - Enny Diah Astuti; Dyan Yuliana; Jajang Setiawan; Ali Satri Efendi; Rahmi Rosita; Retno Setya Budiasningrum (Jurnal Nusantara Berbakti, 2024)
Writing learning contributes to improving students' ability to form relationships between words and sentences as well as relationships between meanings so that they can convey ideas, feelings, critical and logical thoughts through writing. written work made to solve a problem with a theoretical basis and scientific methods. The purpose of this community service program (PkM) is to improve the ability of Teratai Putih Global Islamic High School students through training in writing scientific papers. In the implementation of community service at Teratai Putih Global Islamic High School, the method used is the theory method and group writing practice. Community Service activities carried out by Politeknik LP3I Jakarta lecturers at Teratai Putih Global Islamic High School show the potential to improve students' ability to write scientific papers. One of the skills in organizing and developing ideas or ideas both orally and in writing is the ability to write. It is hoped that this paper can also be published in the future. Students gain academic provision that will be useful for career advancement, self-development, and soft skills of each student.